I believe it’s -12w+16x+20
Hello. 10x-3-2x=4 ; 10x-2x=4+3 ; 8x=7 ; x=7/8. I hope to have helped you
Answer:
1. (2+2)/(-3+4)= 4/1= 4
y + 2 = 4(x + 4)
y + 2 = 4x + 16
y = 4x + 14 y-intercept:(0,14)
2. (0+5)/(-1+2)= 5/1= 5
y + 5 = 5(x + 1)
y + 5 = 5x + 5
y = 5x
y-intercept (0,0)
3. (-1+1)/(-5-3)= 0/-8= 0
y + 1 = 0(x - 3)
y + 1 = 0
y= -1
Answer:
x = ±3 sqrt(2)
Step-by-step explanation:
x^2 + x^2=6^2
Combine like terms
2x^2 = 6^2
Divide each side by 2
x^2 = * 6^2/2
Take the square root of each side
sqrt(x^2) =± sqrt( 6^2/2)
Remember that sqrt(a/b) = ±sqrt(a ) /sqrt(b)
x = ±sqrt(6^2)/sqrt(2)
x = ±6 /sqrt(2)
We do not leave square roots in the denominator, so we multiply the top and bottom by sqrt(2)
x = ±6 /sqrt(2) * sqrt(2)/ sqrt(2)
x = ±6 *sqrt(2) /( sqrt(2)*sqrt(2))
x = ±6 sqrt(2) /(2)
x = ±3 sqrt(2)